2020
DOI: 10.1371/journal.pone.0233852
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for and prediction of post-intubation hypotension in critically ill adults: A multicenter prospective cohort study

Abstract: investigators are given in S1 Table.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 35 publications
3
42
0
1
Order By: Relevance
“…No specific recommendations for type of vasopressor support have been suggested in the literature, though the use of pharmacotherapy to increase afterload and or inotropy during and after the procedure has been articulated [46]. A systolic blood pressure of <130 mmHg prior to intubation is associated with postintubation hypotension in critically ill patients and this threshold will likely apply to COVID19 patients as well [40]. Vasopressor rescue or push doses should be available at the times of intubation, and may include phenylephrine, ephedrine, norepinephrine, and or epinephrine depending on clinical assessment, severity and needs.…”
Section: Hemodynamic Optimizationmentioning
confidence: 99%
“…No specific recommendations for type of vasopressor support have been suggested in the literature, though the use of pharmacotherapy to increase afterload and or inotropy during and after the procedure has been articulated [46]. A systolic blood pressure of <130 mmHg prior to intubation is associated with postintubation hypotension in critically ill patients and this threshold will likely apply to COVID19 patients as well [40]. Vasopressor rescue or push doses should be available at the times of intubation, and may include phenylephrine, ephedrine, norepinephrine, and or epinephrine depending on clinical assessment, severity and needs.…”
Section: Hemodynamic Optimizationmentioning
confidence: 99%
“…An elevated shock index is a specific but insensitive marker of post-intubation hypotension [ 45 47 , 50 53 ]. Recent regression analyses and two recent prediction scores have been developed, which all find that in general, older age, hypotension or shock prior to intubation, intubation for respiratory failure, and higher APACHE score are all strong predictors of post-intubation cardiovascular collapse [ 52 , 54 56 ].…”
Section: Hemodynamicsmentioning
confidence: 99%
“…The investigators identified 11 variables (increasing illness severity; increasing age; sepsis diagnosis; endotracheal intubation in the setting of cardiac arrest, mean arterial pressure < 65 mmHg, and acute respiratory failure; diuretic use 24 h preceding endotracheal intubation; decreasing systolic blood pressure from 130 mmHg; catecholamine or phenylephrine use immediately prior to endotracheal intubation; and use of etomidate during endotracheal intubation) that were independently associated with peri-intubation hypotension with a C-statistic of 0.75 [95% confidence interval (CI): 0.72-0.78]. Of the 11 variables, the use of etomidate was found to protect against peri-intubation hypotension[ 3 ].…”
Section: Introductionmentioning
confidence: 99%